THE CORRELATION BETWEEN THE TEENAGER-PARENTS COMMUNICATION WITH PREMARITAL SEXUAL BEHAVIOR IN ADOLESCENTS AT RW 007 MUSTIKAJAYA KOTA BEKASI IN 2022 - Tina Dwi Hapsari; Meliyana, Ernauli; Deniati, Kiki (Jurnal Medicare, 2022)
Teenage dating behavior has now reached an alarming point, openly displaying affection on social media, in public places, teenagers hug each other affectionately without paying attention to other people around them. Many factors cause premarital sexual behavior, family factors, especially parent-adolescent communication, are one of the most important attitudes and behavior of premarital sex in adolescents. This study aims to determine the teenager-parents communication with premarital sexual behavior in adolescents at RW 007 Mustikajaya Kota Bekasi in 2022. The research method used is quantitative with cross-sectional analytic research. The population in this study were teenagers 12-19 yaer olds at RW 007 Mustikajaya totaling 198 teenagers. The data collection technique used type of purposive sampling based on the inclusion criteria and obtained the number of samples as many as 76 respondents. The results showed that with a significant level of 95% or α value of 5% (0,05) the results of the Chi Square obtained p-value (0,006) < α (0,05). This show that H0 is rejected. The conclusion of the study is a the teenager-parents communication with premarital sexual behavior in adolescents at RW 007 Mustikajaya Kota Bekasi in 2022